AB0316 MULTIPLE SWITCH BETWEEN BIOSIMILARS DMARDs (BSDMARDS) IN PATIENTS WITH INFLAMMATORY ARTHRITIDES: EXPERIENCE OF A SINGLE ITALIAN CENTRE. (2nd June 2020) - Riva, M.; Varisco, V.; Riva, L.; Rumi, F.; Pozzi, M. R.
Abstract : Background: The availability of bsDMARDs since some years represents an opportunity to improve patient access to effective biologic therapy, to better accommodate restraints within healthcare budgets and to improve overall patient outcomes. Different policies are followed in different countries to implement the use of bsDMARDs. Although the latest position paper of AIFA (Agenzia Italiana del Farmaco) envisions the automatic sostitution between the originator and biosimilar, until now the prescriber decision and the patient consent are strongly advised. The question around biosimilar to biosimilar switching is overlooked. Nevertheless different rules are established at regional level and in our Hospital automatic switching between originator/biosimilar and biosimilar/biosimilar was applied. Objectives: To analyze the efficacy and safety of switch from originator to biosimilar (O/B) and/or biosimilar to biosimilar (B/B) in patients with RA, PsA and SpA. Methods: We retrospectively analyzed in 63 patients (30 F, mean age 58.3 yr, 21 RA, 26 PsA, 16 SpA), treated with Infliximab, Etanercept and Adalimumab, disease activity (DAS28 CRP for RA, Tender/Swollen joint count for PsA, BASDAI for SpA, CRP for all) and adverse events/infections (AE). The time points considered were 3 rd month before the switch and 3 rd and 6 th month after. Results: 45 patients underwent sigle switch (35 O/B, 9 B/B) and 18 (28.5%) double switch (O/B/B). 27 B/B switch were done. No differences in disease activity were observed before and after switch (8 RA patients: mDAS28 CRP 2.86>3.23, 11 PsA patients: mTJ count 2.5 > 3.43, 8 SpA patients: BASDAI 2.88 > 2.84). The mean number of swollen joints was very low in PsA group and we decided to exclude this variable. The CRP level was low and stable along all period examined in the three groups. No increase in steroid daily dose, nor in concomitant DMARDs therapy was reported. In the Etanercept B/B switch (14 pts) the number of infections was the same before (3) and after (3). In Infliximab B/B switch (13 pts) 3 infections were reported only before the switch. The severity was mild/moderate with prevalence of respiratory infections (57%). No remarkable variation of transaminases and blood counts were observed. Conclusion: Althoug the population we examined was eterogeneous and quite small, we observed that the efficay and safety of Infliximab and Etanercept are maintained with biosimilar to biosimilar switch, also after double switch (originator>biosimilar>biosimilar). We also can confirm that the switch from originator to biosimilar Infliximab, Etanercept and Adalimumab is safe in our experience. Disclosure of Interests: None declared